2006
DOI: 10.1063/1.2409689
|View full text |Cite
|
Sign up to set email alerts
|

Current rectification by asymmetric molecules: An ab initio study

Abstract: Current rectification effect in an asymmetric molecule HCOO-C6H4-(CH2)n sandwiched between two aluminum electrodes has been studied using an ab initio nonequilibrium Green's function method. The conductance of the system decreases exponentially with the increasing number n of CH2. The phenomenon of current rectification is observed such that a very small current appears at negative bias and a sharp negative differential resistance at a critical positive bias when n>or=2. The rectification effect arises from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Within the last decade, Kornilovitch et al, 33 Bratkovsky et al, 34 Liu et al, 35 Xu et al, 36 and Stokbro, 33 have suggested that a D-σ-A structure is not required for molecular rectification, but that rectification can be achieved with a single, localized, accessible Recently, we and others have realized an experimental demonstration of a rectifier that incorporates a ferrocene group-S(CH 2 ) 11 Fc (Fc = ferrocene)-and have given evidence that the rectification has a molecular origin 23 and is dependent on asymmetric placement of the Fc moiety between the electrodes. alkanethiols (used as controls).…”
Section: Iii) Potential For Redoxmentioning
confidence: 99%
“…Within the last decade, Kornilovitch et al, 33 Bratkovsky et al, 34 Liu et al, 35 Xu et al, 36 and Stokbro, 33 have suggested that a D-σ-A structure is not required for molecular rectification, but that rectification can be achieved with a single, localized, accessible Recently, we and others have realized an experimental demonstration of a rectifier that incorporates a ferrocene group-S(CH 2 ) 11 Fc (Fc = ferrocene)-and have given evidence that the rectification has a molecular origin 23 and is dependent on asymmetric placement of the Fc moiety between the electrodes. alkanethiols (used as controls).…”
Section: Iii) Potential For Redoxmentioning
confidence: 99%
“…The conductance of stilbene at E F decreases exponentially as the gold electrodes length increases. An exponential decrease of conductance with an increasing length of an electrode has been reported in the literature [52]. Therefore, a suitable length of Au-electrode must be selected to explore the transport characteristics of a stilbene device.…”
Section: Transport Properties Of Sms Devicementioning
confidence: 97%
“…Charged amino acids are the major determinants of the recti cation of gap junctional channel [19] and short-range ET and ETp [20]. Current recti cation is observed in asymmetric molecule structures [21][22][23][24] and due to the moleculeelectrode coupling [25].…”
Section: Introductionmentioning
confidence: 99%